Mast cell biology contemporary and emerging topics - Gilfillan, Alasdair M.; Metcalfe, Dean D.; SpringerLink (Online service). (Boston, MA Springer, 2011)
The editors of Mast Cell Biology, Drs. Gilfillan and Metcalfe, have enlisted an outstanding group of investigators to discuss the emerging concepts in mast cell biology with respect to development of these cells, their homeostasis, their activation, as well as their roles in maintaining health on the one hand and on the other, their participation in disease.
Mast Cell Biology: Introduction And Overview -- Mast Cell Progenitor Trafficking And Maturation -- Monomeric IgE And Mast Cell Development, Survival And Function -- Mast Cell Apoptosis And Survival -- Regulators Of Ca2+ Signaling In Mast Cells: Potential Targets For Treatment Of Mast Cell-Related Diseases -- Spatio-Temporal Signaling In Mast Cells -- The Mechanisms Of Exocytosis In Mast Cells -- An Emerging Role For The Lipid Mediator Sphingosine-1-Phosphate In Mast Cell Effector Function And Allergic Disease -- Down-Regulation Of Mast Cell Responses Through Itim Containing Inhibitory Receptors -- The Mast Cell In Innate And Adaptive Immunity -- Mast Cells And Immunoregulation/Immunomodulation -- Mast Cell Proteases As Protective And Inflammatory Mediators -- Mast Cells In Lung Inflammation -- Mast Cells, Angiogenes Is And Cancer.
College of Science Library has electronic copy. Kindly send us a message through cslib@science.upd.edu.ph using your UP mail for the copy of this material.
Electronic reproduction.
Keywords: Mast cells; Electronic books